2015
DOI: 10.1088/0004-637x/804/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in Plain Sight: An Abundance of Compact Massive Spheroids in the Local Universe

Abstract: It has been widely remarked that compact, massive, elliptical-like galaxies are abundant at high redshifts but exceedingly rare in the Universe today, implying significant evolution such that their sizes at z ∼ 2 ± 0.6 have increased by factors of 3 to 6 to become today's massive elliptical galaxies. These claims have been based on studies which measured the half-light radii of galaxies as though they are all single component systems. Here we identify 21 spheroidal stellar systems within 90 Mpc that have half-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 271 publications
5
75
0
1
Order By: Relevance
“…Based on their results, Noeske et al (2006) suggested that the majority of BSph galaxies at high-z will evolve into small disk galaxies or low-mass spheroids 2 . They neither find any evidence suggesting inside-out growth scenario which could turn BSphs to large disks, nor do they see any disk growth around BSphs (but see Graham, Dullo, & Savorgnan 2015;Graham, Ciambur, & Savorgnan 2016;Graham et al 2017, for an alternative view). Lopes et al (2016) also investigated a sample of low-z galaxies in various environments.…”
Section: Introductionmentioning
confidence: 93%
“…Based on their results, Noeske et al (2006) suggested that the majority of BSph galaxies at high-z will evolve into small disk galaxies or low-mass spheroids 2 . They neither find any evidence suggesting inside-out growth scenario which could turn BSphs to large disks, nor do they see any disk growth around BSphs (but see Graham, Dullo, & Savorgnan 2015;Graham, Ciambur, & Savorgnan 2016;Graham et al 2017, for an alternative view). Lopes et al (2016) also investigated a sample of low-z galaxies in various environments.…”
Section: Introductionmentioning
confidence: 93%
“…Simultaneously, the already existing quenched galaxies may also grow in size (horizontal red arrow) either by minor merging 13 or perhaps by accreting stars (and/or gas) that could rebuild a disk, which in some cases could host some star formation (diagonal up, not shown), and eventually lead to the formation of early-type (passive) disks (e.g., Bundy et al 2010;MargalefBentabol et al 2016), which nonetheless maintain the same stellar density within the central 1 kpc. The disk regrowth scenario could explain the apparent decline in the number of the most compact quiescent galaxies (defined as having small sizes of r 1 2 e < -kpc) with time (e.g., Cassata et al 2013;Damjanov et al 2014Damjanov et al , 2015Trujillo et al 2014;Ferré-Mateu et al 2017) since they would be hidden as the bulges of today's massive early-type disks (Driver et al 2013;Graham & Scott 2013;Graham et al 2015).…”
Section: Galaxy Morphologies In the Sfrmentioning
confidence: 99%
“…Are elliptical galaxies simply naked bulges and are bulges related to high-redshift compact galaxies (e.g. Graham et al 2015;Berg et al 2014)? Are the discs of early-types, late-types and irregulars indistinguishable?…”
Section: Introductionmentioning
confidence: 99%